Pregnancy Anxiety Levels and Related Factors in Women Undergoing Caesarean Section - Simanjuntak, Leo; Simanjuntak, Patrick Anando (Universitas Muhammadiyah Sumatera Utara, 2022)
Abstract: Anxiety is the most common psychiatric disorder in pregnancy. Anxiety in pregnancy is related to preterm labor, fetal growth restriction, and poor neurobehavioral development. Anxiety before cesarean section can increase the need for anesthesia, postoperative analgesics, and cause an immunocompromised condition. This study aimed to assess the maternal anxiety level and related factors during caesarean section. This is a cross-sectional study using primary data from a private maternity clinic in April-May 2020. Based on defined criteria, 117 subjects were recruited for this study. Anxiety levels are assessed using the Hamilton Anxiety Rating Scale (HAM-A). Logistic regression was used to identify factors associated with anxiety level. age was 29.445.90 years. The mean HAM-A score was 9.905.80 points. High scoring HAM-A components were the anxious mood component (1.560.74), insomnia (sleep disturbance) (1.400.67), and tension (1.380.73). A majority of the pregnant women (76.9%) showed no anxiety about undergoing caesarean section. The rest of these pregnant women (23.1%) showed mild anxiety (13.7%) and moderate anxiety (9.4%). There was no statistically significant correlation between age, education background, income level, parity level, occupation, and history of caesarean section. Adequate analgesics, family support, and informative and educative advice about caesarean section can make pregnant women not worried about this procedure.Keywords:Anxiety; Pregnancy; Caesarian Section; HAM-A